Screening of two freshwater green microalgae in pulp and paper mill wastewater effluents in Nova Scotia, Canada - Shabana Bhatti (IWA Publishing, 2021)
In recent years, the use of microalgae as feedstock for many marketable products, such as animal/aqua feeds, bioplastics and fertilizers, has gained renewed interest due to their fast growth potential coupled with relatively high lipid, carbohydrate and nutrient content. An algal biorefinery at an industrial site has the potential to sustainably and profitably convert carbon dioxide emissions into microalgal biomass and concomitantly reduce nitrogen and phosphorus from wastewaters. Industrial wastewaters are a potential alternative to traditional media used for large-scale microalgal cultivation. Pulp and paper mills are major consumers of water resources and discharge a huge amount of water to nearby lakes or rivers. This study investigated whether pulp and paper mill waste water is suitable for microalgal cultivation with the aim of achieving significant biomass production. Six different process waters from one Canadian pulp and paper mill were tested with two freshwater green microalgae. All of these waters were unable to support growth of microalgae due to inadequate nutrient concentrations, colour, turbidity and possible toxicity issues. HIGHLIGHTS Two freshwater microalgae strains were screened for potential growth on pulp and paper effluents.; Pulp and paper wastewater effluents were unable to support growth of the microalgae.; Chemical residues from the pulping process, such as peroxide and tannin, may inhibit algal growth.;